Mechanical alignment changes during flexion in total knee arthroplasty without affecting clinical outcomes. (February 2020) - Giorgini, Andrea; Zambianchi, Francesco; Lombardi, Martina; Francioni, Elena; Marcovigi, Andrea; Catani, Fabio
Abstract: Background: Primary aim of this study is to investigate if Hip-Knee-Ankle angle, measured in the coronal plane, changes with knee flexion after total knee arthroplasty. The secondary aim is to assess the relationship between Hip-Knee-Ankle during knee flexion and clinical outcome at mid-term follow up. Methods: 334 computer assisted total knee arthroplasties were retrospectively evaluated. A total of 233 patients were available for assessment of clinical outcomes at last follow up (mean 35 months). Hip-Knee-Ankle angle at different degrees of knee flexion and components' alignment were recorded intraoperatively. Findings: Patients were stratified based on the preoperative alignment: 202 varus knees, 99 neutral knees, and 33 valgus knees. In the varus knee group, 146 patients (89%) maintained a neutral overall limb alignment when flexed to 20°, 118 (72%) remained neutrally aligned at 45° and 92 (54%) at 90°. In valgus knee group, 26 (90%) remained neutrally aligned at 20°, 22 (75%) at 45° and 16 (55%) at 90°. In neutrally-aligned knee group, 88 (96%) remained neutrally aligned at 20°, 73 (79%) at 45° and 61 (66%) at 90°. Femoral component external rotation was correlated with varus alignment in flexion. Good outcomes were reported in 181 (78%) cases, fair results in 28 (12%) cases, poor results in 24 (10%) of cases. Poor results were not correlated to Hip-Knee-Ankle angle at different knee flexion angles. Interpretation: This study demonstrates that intraoperative Hip-Knee-Ankle angle changes as the knee moves into deeper flexion. However, neutral Hip-Knee-Ankle through the range of motion does not correlate with superior outcomes. Highlights: Hip-Knee-Ankle angle changes during flexion in total knee arthroplasty. Clinical outcome is not affected by mechanical axis at different degrees of flexion. This study questions the importance of neutral mechanical alignment in extension.